Global Supply Chains and Geopolitical Realism: Huawei’s Survival Strategy against the US Ban - Wijayati, Hasna; Murdani, Andika Drajat (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The US policy of isolating the Chinese technology company Huawei has significantly transformed the company’s global business operations. This conflict extends beyond business interests, touching on broader geopolitical dynamics between states. This research aims to examine the impact of the US ban on Huawei’s global supply chain and analyze how the company has adapted through strategic responses. Employing a descriptive qualitative method with a literature study approach, this study analyzes secondary data from various sources. Two main theoretical frameworks guide the analysis: Global Supply Chain Theory, which explores Huawei's dependency on US-origin technological components, and Realism Theory in International Relations, which interprets US actions as an effort to maintain its hegemonic position in the global technological order. The findings reveal that the US ban significantly disrupted Huawei's access to critical technologies, especially semiconductor chips. In response, Huawei adopted a survival strategy centered on supply chain diversification and domestic innovation. The research concludes that although the ban caused substantial short-term setbacks, Huawei demonstrated resilience through long-term strategic adaptation. The novelty of this study lies in its integration of political economy and international relations perspectives to explain how a global technology company navigates geopolitical pressures and supply chain vulnerabilities.